Padova 1990 - Autori vari (Il sogno della farfalla, 2024)
On the 24th and 25th February 1990 the international congress titled "The syndrome of schizophrenic apathy between phenomenological conceptions and the world of scales" took place at the University of Padua, attended by leading Italian and foreign scholars. That was one of the first occasions in which psychiatrists of the Fagioli’s approach proposed their research, developed together with the author of the Human Birth Theory, in an international scientific context. We republish those conference reports today not only for their historical significance but above all for the relevance of the psychiatric and psychopathological elaborations they proposed.